Digitalization and digital transformation in higher education: A bibliometric analysis - Díaz-García, Vicente; Montero-Navarro, Antonio; Rodríguez-Sánchez, José-Luis; Gallego-Losada, Rocío (Frontiers in Psychology, 2022)
The new paradigms that are emerging because of technological and social advances derived from the massive use of information and communication technologies (ICTs) are generating a transformative process that is modifying all economic sectors, and education is no exception. Higher Education Institutions (HEIs) are carrying out such transformation, reacting to the need of adaptation to this new reality, experiencing a complete cultural change that is challenging the attitudes, actions and values shared by the members and stakeholders of these organizations. In order to analyze the scientific literature about this topic, a bibliometric analysis has been carried out covering the period 1900–2021, considering a sample of 469 articles included in the Web of Science (WoS) database. The results show the multidisciplinary nature of the topic, including articles published in different areas, as well as its close link with aspects such as innovation, governance and agile methodologies. Finally, this study highlights the main lines of research that could attract more attention in the immediate future.